Dynamic Characteristics of Bidirectional Misaligned Marine Water-Lubricated Bearings Considering Turbulence, Surface Roughness and Bush Deformation - Ziqi Chen; Ji Wang; Rui Li; Yujun Liu (Journal of Marine Science and Engineering, 2025)
The marine water-lubricated bearing’s (WLBs) dynamic properties are essential for ensuring the shaft system’s operational dependability. The coupled model of mixed lubrication and turbulence under the impact of bidirectional misalignment is proposed in this research, and the perturbation equations of marine WLBs with 32 coefficients are derived. The finite difference method (FDM) is used to solve the steady-state and perturbation equations, and the impacts of turbulence, bearing bush deformation, surface roughness, and bidirectional shaft misalignment on the dynamic characteristics of the WLBs are systematically investigated. The results reveal that under mixed lubrication, surface roughness and the turbulence effect can both greatly improve the stiffness and damping of the bearings, but that there is a threshold phenomenon for the turbulence effect’s influence on these properties. Neglecting the elastic deformation of the bush may lead to an overestimation of the bearings’ stiffness and damping, causing substantial inaccuracies in conditions of heavy load or declined Young’s modulus. The 32 coefficients of the WLB exhibit considerable variation with the misalignment angle; hence, a more comprehensive dynamic model should be developed for misaligned marine WLBs. The study’s findings provide valuable insights for rotor dynamics research and optimal design of lubrication performance in marine WLBs.